2022
DOI: 10.33899/ijvs.2022.132660.2119
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of virulence genes of Pseudomonas aeruginosa isolated from fish (Cyprinus carpio) in Mosul city

Abstract: Depending on the nature of the fish's environment, they are susceptible to many pathogens, including bacterial causes, so the goals of the current study are isolation and molecular identification of Pseudomonas aeruginosa with its prevalence rate and detected virulence genes from fresh common carp fish. The swabs were taken from the gills, skin, intestine and muscles of 75 fish samples from variable localities from Mosul city during the period September to December in the year 2021. The prevalence percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The microbial load was highest (gills and fins) and may be attributed to the highest ambient river temperature. Microbial load in fish may rise with increasing temperature of water [16,17].In study [18] acquired eighty isolates of P. aeruginosa from samples of fish market specimens' gills, skin, gut, and muscles. The gills had the largest proportion of isolation at 42.5%, followed by the skin at 37.5%, the intestine at 15%, and the muscles at 5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbial load was highest (gills and fins) and may be attributed to the highest ambient river temperature. Microbial load in fish may rise with increasing temperature of water [16,17].In study [18] acquired eighty isolates of P. aeruginosa from samples of fish market specimens' gills, skin, gut, and muscles. The gills had the largest proportion of isolation at 42.5%, followed by the skin at 37.5%, the intestine at 15%, and the muscles at 5%.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum sensitivity of drug screening in different organisms is a reasonable technique that can significantly reduce the dose of antibiotics. After starting therapy, isolates that were initially susceptible or intermediately resistant to one antibiotic may develop resistance [18].Ipenem and gentamicin were both ineffective against 96% of the isolates, whereas doxycycline, ciprofloxacin, trimethoprim-sulfamethoxazole, norfloxacin, and ceftriaxone were next in line. None of them were levofloxacin-resistant on Disease Aeromonas hydrophila [21].…”
Section: Discussionmentioning
confidence: 99%
“…(30). A study reported that the lethal concentrations of CuSO4 at 10 mg/l led to killing the fish, and mortality was 100% during 24 hours, while the concentration at five mg/l was the median lethal concentration which led to killing 50% of treated fish (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The electrophoresis condition was set at 80 V, 300 mA ,50 min by using Wide Mini-Sub Cell GT gel electrophoresis systems and basic power supply (Bio-Rad, USA), A 4 µl of 100 bp DNA ladder, (GeNet Bio, Korea) was used as molecular weight standard. After that, the gel was viewed using Gel doc Ez system to detect the specific bands (18,19).…”
Section: Detection Of E Coli and Their Esbl Gene By Pcr Reaction Methodsmentioning
confidence: 99%